A gold mine, but still no Klondike: Nordic register data in health inequalities research - Van Der Wel, Kjetil A. (Scand J Public Health, 2019)
Aims: Future research on health inequality relies on data that cover life-course exposure, different birth cohorts and variation in policy contexts. Nordic register data have long been celebrated as a ‘gold mine’ for research, and fulfil many of these criteria. However, access to and use of such data are hampered by a number of hurdles and bottlenecks. We present and discuss the experiences of an ongoing Nordic consortium from the process of acquiring register data on socio-economic conditions and health in Denmark, Finland, Norway and Sweden. Methods: We compare experiences of data-acquisition processes from a researcher’s perspective in the four countries and discuss the comparability of register data and the modes of collaboration available to researchers, given the prevailing ethical and legal restrictions. Results: The application processes we experienced were time-consuming, and decision structures were often fragmented. We found substantial variation between the countries in terms of processing times, costs and the administrative burden of the researcher. Concerned agencies differed in policy and practice which influenced both how and when data were delivered. These discrepancies present a challenge to comparative research. Conclusions: We conclude that there are few signs of harmonisation, as called for by previous policy documents and research papers. Ethical vetting needs to be centralised both within and between countries in order to improve data access. Institutional factors that seem to facilitate access to register data at the national level include single storage environments for health and social data, simplified ethical vetting and user guidance.